The Impact of Islam on Malaysia Before Independence - Abdul Rahman, Sadiqa binti (Journal Of Middle East and Islamic Studies, 2024)
This article discusses the influence and significance of the introduction of Islam in the Malaya on Malays before achieving independence. Prior to the advent of Islam, the Malaya was heavily influenced by several belief systems, including Hinduism, Animism, Buddhism, Dynamism, Hyang, and others. Nevertheless, Malaya, like other regions influenced by Islamic Civilization, has embraced the Sunnah teachings of Prophet Muhammad. Since 12 AD, the way of life in Malaya has been firmly rooted in Islamic teachings. The research objectives are to examine the general background of Malaysia and analyse the impact of the arrival of Islam in Malaya on the Malay people. The name change from Malaya to Malaysia occurred on September 16, 1963. Before this date, the region was known as the Federation of Malaya. On September 16, 1963, Malaysia was formed through the amalgamation of the Federation of Malaya with the former British colonies of Singapore, North Borneo (now Sabah), and Sarawak. This qualitative research employs a historical study and content analysis approach. Analysis of research data is conducted using a thematic and deductive approach. Research results reveal that there are four main effects of the role of the arrival of Islam in Malaysia to the Malays. Undoubtedly, the advent of Islam has exerted a profound influence on the realms of politics, social dynamics, education, and legislation among the Malays even prior to their attainment of independence.